Pengaruh Pendidikan Kesehatan terhadap Fungsi Perawatan Kesehatan Keluarga dengan Tuberkulosis Paru: Laporan Kasus - Zahra, Muna Az; Lukman, Mamat; Sari, Sheizi Prista (REAL in Nursing Journal, 2024)
Background: Tuberculosis (TB) is a public disease that can be transmitted through air transmission, resulting in high morbidity and mortality in developing countries. Increased TB transmission due to poor health care functions for families with pulmonary TB. Providing health education is an effort to increase family awareness so the aim of this research is to determine the effect of health education on the health care function of families with pulmonary TB. This study used a descriptive design, namely a case report, on 1 family with pulmonary TB problems for 10 days and a health education intervention with a family health care function approach. After health education was carried out, there was an increase in knowledge and good behavior in families regarding the care and prevention of pulmonary TB transmission so that the family's health care function also showed a corresponding increase. In conclusion, health education can influence the function of family health care in the treatment and prevention of pulmonary TB because good knowledge shows good behavioral changes accompanied by family confidence and awareness to improve the health status of the family together.